2022
DOI: 10.3389/fimmu.2022.1076245
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum potentially improves inflammation and immunity through alteration of the microbiota and metabolism of gastric cancer patients after gastrectomy

Abstract: BackgroundGastrectomy is the most effective treatment to improve the clinical survival rate of patients with gastric cancer. However, the pathophysiological changes caused by gastrectomy have seriously affected the postoperative recovery.MethodsIn the present trial, Ataining (containing C. butyricum, CGMCC0313.1) was applied in patients after gastrectomy to investigate the effect of C. butyricum on the early postoperative recovery by monitoring the inflammatory immune response with blood indicators, detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…48 Furthermore, Desulfovibrio is a pathogenic bacterium that can cause bacteremia. 49 The present study showed that SA intervention reduced the abundance of norank-f-Oscillospiraceae, Ruminococcus and Desulfovibrio. Therefore, the improved immunosuppressive function of SA may be related to its regulation of the ratio of beneficial and harmful bacteria.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…48 Furthermore, Desulfovibrio is a pathogenic bacterium that can cause bacteremia. 49 The present study showed that SA intervention reduced the abundance of norank-f-Oscillospiraceae, Ruminococcus and Desulfovibrio. Therefore, the improved immunosuppressive function of SA may be related to its regulation of the ratio of beneficial and harmful bacteria.…”
Section: Discussionsupporting
confidence: 55%
“…Clinical studies have found a higher abundance of Ruminococcus in the gut of patients with inflammatory bowel diseases compared to healthy populations 48 . Furthermore, Desulfovibrio is a pathogenic bacterium that can cause bacteremia 49 . The present study showed that SA intervention reduced the abundance of norank‐f‐Oscillospiraceae , Ruminococcus and Desulfovibrio .…”
Section: Discussionsupporting
confidence: 47%
“…We speculate that the synbiotic used in the present study has therapeutic potential, and may represent a promising means of preventing hyperuricemia and hyperammonemia in patients with cirrhosis. Additionally, the synbiotic supplementation also increased the butyric acid concentration in peripheral blood, which is considered beneficial to immune homeostasis in the other clinical trial (Cao et al, 2022). Although these findings imply that synbiotics are beneficial for patients with cirrhosis, further large human studies and animal experiments should be conducted to determine whether and how synbiotics affect key pathways.…”
Section: Discussionmentioning
confidence: 94%
“…We speculate that the synbiotic used in the present study has therapeutic potential, and may represent a promising means of preventing hyperuricemia and hyperammonemia in patients with cirrhosis. Additionally, the synbiotic supplementation also increased the butyric acid concentration in peripheral blood, which is considered beneficial to immune homeostasis in the other clinical trial ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the use of probiotics in gastric cancer patients only postoperatively (starting 3–5 days after gastrectomy) showed a notable effect in reducing the inflammatory process provoked by surgery and enhancing existing immunity. This was shown by the important reduction of leukocytes, interleukin-1β (IL-1β), IL-6, and TNF-α and increased levels of immunoglobulin A and immunoglobulin M in the serum [ 94 ].…”
Section: Resultsmentioning
confidence: 99%